MIDDLE MIOCENE BIOSTRATIGRAPHY AND PALEO-OCEANOGRAPHY OF SUPIORI ISLAND, PAPUA BASED ON CALCAREOUS NANNOFOSIL ASSEMBLAGES - Ryan Dwi Wahyu Ardi; Nadila Novandaru; Istiana Istiana; Alviyanda Alviyanda; Rubiyanto Kapid; G.M. Lucky Junursyah; Rahmat Y Saragih (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2019)
Calcareous nannofossil assemblages have been analysed from three stratigraphic sections on Supiori Island to determine biozonation and paleo-oceanographic condition. Based on Neogene Calcareous Nannofossils Zonation (Martini, 1971), section BK 78 (Wainukendi Formation) classified into three zones, which coeval to NN7–NN9 and or younger (Middle Miocene). Section BK 95 (Napisendi Formation) categorised into five zones, which equivalent to NN5–NN9 (Middle Miocene), and section BK 98 (Wafordori Formation) is considered to be equivalent to NN7 (Middle Miocene). Those results indicate a correlatable interval (NN7) and an interfinger contact between Wainukendi, Wafordori, and Napisendi Formations. Paleo-oceanographic parameters namely thermocline/nutricline depth and paleosalinity were analysed in this research. Thermocline/nutricline depth analysis from Discoaster abundance and mean coccolith size of Reticulofenestra and Coccolithus indicate sea surface condition changes from oligotrophic (NN5–NN7) to eutrophic (early NN8) and then again into oligotrophic (from late NN8 to NN9). Paleosalinity analysis based on abundance comparison between Sphenolithus neoabies, Helicosphaera carteri, and Calcidiscus leptoporus denotes paleosalinity shift from normal saline (NN7) to hyposaline condition (NN8 – NN9). Those paleo-oceanographic parameters changes most likely related to the closing of Indonesian Seaway due to regional uplift, which triggered the formation of proto West Pacific Warm Pool (WPWP), Equatorial Under Current (EUC), and eventually a La Nina-like condition on late Middle Miocene (NN8–NN9).